2017
DOI: 10.1515/tnsci-2017-0018
|View full text |Cite
|
Sign up to set email alerts
|

The arcuate fasciculus network and verbal deficits in psychosis

Abstract: BackgroundVerbal learning (VL) and fluency (VF) are prominent cognitive deficits in psychosis, of which the precise neuroanatomical contributions are not fully understood. We investigated the arcuate fasciculus (AF) and its associated cortical regions to identify structural abnormalities contributing to these verbal impairments in early stages of psychotic illness.MethodsTwenty-six individuals with recent-onset psychosis and 27 healthy controls underwent cognitive testing (MATRICS Consensus Cognitive Battery) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…Additionally, studies reported syntactic deficits in patients with primary progressive aphasia after damage of arcuate fasciculus suggesting that the role of this tract is not limited to single word processing (Wilson, Galantucci, Tartaglia, & Gorno‐Tempini, ). More recently, studies suggested a possible correlation between right hemisphere arcuate fasciculus abnormalities and deficit in VF in psychosis (Kenney et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies reported syntactic deficits in patients with primary progressive aphasia after damage of arcuate fasciculus suggesting that the role of this tract is not limited to single word processing (Wilson, Galantucci, Tartaglia, & Gorno‐Tempini, ). More recently, studies suggested a possible correlation between right hemisphere arcuate fasciculus abnormalities and deficit in VF in psychosis (Kenney et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…While DTI-based fiber tractography (Mori et al 1999;Basser et al 2000) is still the most widely used approach in a clinical setting, there are nowadays more accurate approaches to compute fiber orientations, such as those based on spherical deconvolution approaches (Tournier et al 2007;Dell'Acqua et al 2010;Tax et al 2014;Jeurissen et al 2019). In regions with crossing fiber configurations, these advanced tractography techniques have been shown to provide more reliable reconstructions of white matter fiber pathways (Jeurissen et al 2011;De Schotten et al 2011;Thiebaut de Schotten et al 2012;Rojkova et al 2016;Kenney et al 2017). In this context, scalar measures derived from DTI, such as the mean diffusivity or the FA used in this work, are also non-specific in regions with multiple crossing fiber pathways and are prone to partial volume effects (Vos et al 2011(Vos et al , 2012Jeurissen et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, results of the hierarchal regression analysis indicated an association between total CRI and right pars orbitalis, a region whose functional role is still debated. Some indications of the relationship between right pars orbitalis and verbal learning and fluency has been found in patients in early stages of psychotic illness, but not in controls (Kenney et al, 2017). While there is a gap in studies considering pars orbitalis in the non-dominant hemisphere, studies including the right inferior frontal gyrus -area within which lays pars orbitalis -has been shown to be vulnerable to different types of dementia and thus might benefit from lifestyle activities or interventions (Schroeter et al, 2012).…”
Section: Discussionmentioning
confidence: 99%